Large‐Grain Formamidinium PbI3–xBrx for High‐Performance Perovskite Solar Cells via Intermediate Halide Exchange. Issue 12 (30th January 2017) - Long, Mingzhu; Zhang, Tiankai; Xu, Wangying; Zeng, Xiaoliang; Xie, Fangyan; Li, Qiang; Chen, Zefeng; Zhou, Fengrui; Wong, Kam Sing; Yan, Keyou; Xu, Jianbin
Abstract : Deliberate halide exchange between unstable intermediate HPbI2 Br and nonstoichiometric FAI is employed to produce high‐quality FAPbI3– x Br x ( x ≈ 0.44), which eliminates the use of antisolvent dripping and other post‐treatment techniques. The obtained perovskite thin film demonstrates high crystallinity and a large and compact crystal domain up to 2–3 µm. The corresponding device shows power conversion efficiency of up to around 19.0%, with reliable stability and reproducibility.